Twyla & the Tharpettes Donald Hutera at Tharp's The One Hundreds - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 1998)
Donald Hutera goes behind the scenes - and hits the stage - in a revival of Twyla Tharp's funky, mathematical community blockbuster. PALABRAS CLAVE: The One Hundreds, Twyla Tharp.